Pemikiran Pendidikan Islam Muhammad Iqbal Dan Relevansinya Dengan Pendidikan Akhlak - Jaelani, Juhri; Alkausar, Muhammad Miftah; Alby, Muhammad Makhareja Sidqi (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
Moral education has become very important amid rapid advances in technology and information. Moral decline can be seen in the prevalence of hate speech, hoaxes, and so on. One connection to moral improvement and development can be found in the concept of education developed by philosopher Muhammad Iqbal. This study aims to explore Muhammad Iqbal's concept of Islamic education and its relevance to moral education. The research employs a descriptive qualitative approach using library research as the data collection method. The data analysis techniques involve reading, understanding, analyzing, identifying, and comparing Muhammad Iqbal's educational concepts and their relevance to moral education. The results of the study indicate that Muhammad Iqbal's concept of Islamic education is to produce a person of perfect moral character (insan kamil), that is, a person who embodies divine attributes within themselves. This aligns with the purpose of moral education in Islam, which is that the best of humanity is the one with the best moral character.